MANAJEMEN KERJA KEPALA MADRASAH DALAM MENERAPKAN BUDAYA ISLAMI DI MAS SALIMPAUNG KABUPATEN TANAH DATAR - Zulhendri Zulhendri; Hasan Zaini; Marjoni Imamora (IAIN Batusangkar, 2019)
The departs from the constraints of the MAS Salimpaung in applying discipline specifically Islamic culture is the students are required to practice all the theories that have been learned to be practiced in their daily lives at school. Such as the obligation to shake hands by kissing hands before entering class, performing dhuha prayer, midnight prayer in congregation, and checking each student's activities in the form of Islam, both in the school environment and outside the school environment. Islamic culture is formed wherever students are. The formulation of Working Management of Head Master in Implementing Islamic Culture at MAS Salimpaung, is carried out by the foundation, committee and several related teachers. The results of the formulation are: routine, spontaneous, exemplary and conditioning activities. The formulation was carried out in the school by experiencing 3 obstacles, namely, there was no reference to the program as a comparison, it was not presented by people who were experienced in formulating and lacking precisely the time of deliberation, because it was carried out in the afternoon. Working management implementation of Head Master in Implementing Islamic Culture, that, routine activities that run at MAS Salimpaung such as every morning, pray before and after lessons, Dhuha prayer, memorizing letters, and midday prayers. This activity includes daily activities, while weekly activities such as muhadharah are attended by all monthly school residents such as every three months a student and teacher tent is held. Annual activities such as mabid in the month of Ramadan, the celebration of Idul Fitri adn Idul Adha. (3). The evaluate method of Working Management of Head Master in Implementing Islamic Culture at MAS Salimpaung is carried out by examining more deeply the constraints found in the field, as well as holding a monthly evaluation meeting with the MAS Salimpaung Foundation.